THE CYTOTOXIC AND PROLIFERATIVE ACTIVITY OF COCOA POD HUSK EXTRACT (THEOBROMA CACAO L.) ON PERIODONTAL LIGAMENT FIBROBLASTS - Rahayu, Yani Corvianindya; Triwahyuni, Iin Eliana; Kusumawardani, Banun; Sari, Dewi Yunita (Odonto : Dental Journal, 2022)
Background: Theobroma cacao was considered agricultural wastes. Cocoa pod husk contain various bioactive compounds as natural antioxidants,antibacterial and anti-inflammatory. A good biomaterial must be non-toxic and have no detrimental effect on the biological environment. The aim of research was to determine the cytotoxicity and proliferative activity of cocoa pod husk extract on primary cells of periodontal ligament fibroblasts. Method: This experimental laboratory used primary cell culture of periodontal ligament fibroblasts. The cytotoxicity and proliferative activity were analyzed by MTT assay [2-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide]. Extraction of cacao pods were obtained using the ultrasonic homogenizer method with ethanol 70%. The cytotoxicity test was observed for 24 hours and the doubling time proliferative test was observed for 24, 48, and 72 hours. Result: Cocoa pod husk extract showed there were no cytotoxic effects with viability of primary cells of periodontal ligament fibroblasts at the concentration of 1.56 pg/ml, 3.125 pg/ml, 6.25 pg/ml, 12.5 pg/ml, 25 pg/ml, 50 pg/ml, and 100 pg/ml. The proliferation test showed increasing of fibroblasts at 24 and 48 hours. Kruskal Wallis analysis obtained a significance value (p<0.05) Conclusion: Cytotoxicity and proliferation assays of Cocoa pod husk extract increased cell viability and cell proliferation of periodontal ligament fibroblast.